The effects of omega‐3, DHA, EPA, Souvenaid® in Alzheimer's disease: A systematic review and meta‐analysis - Ernesto Calderon Martinez; Stephin Zachariah Saji; Jonathan Victor Salazar Ore; Omar A. Borges‐Sosa; Samyuktha Srinivas; Naga Sai Rasagna Mareddy; Tanseem Manzoor; Mariela Di Vanna; Yasemin Al Shanableh; Rishabh Taneja; Victor Sebastian Arruarana (Wiley, 2024)
Abstract Background Alzheimer's disease (AD) is the most common cause of dementia worldwide. Omega‐3 fatty acids (n‐3‐PUFA) are essential to normal neural development and function. Souvenaid®, a medical supplement that contains n‐3‐PUFA's: eicosatetraenoic acid (EPA) and docosahexaenoic acid (DHA), has emerged as an alternative, slowing cognitive decline in AD patients. In this study, we investigated the effect of dietary supplementation with n‐3‐PUFA, EPA, DHA, and Souvenaid® in AD patients. Aim This systematic review and meta‐analysis aim to establish the relationship between n‐3‐PUFA, EPA, DHA, and Souvenaid® with cognitive effects, ventricular volume and adverse events in AD patients. Methods A systematic search of randomized control trials (RCT), cohorts, and case-control studies was done in PubMed, Scopus, Web of Science, Cochrane, and Embase for AD adult patients with dietary supplementation with n‐3‐PUFA, EPA, DHA, or Souvenaid® between 2003 and 2024. Results We identified 14 studies with 2766 subjects aligned with our criteria. Most publications described positive cognitive outcomes from supplements (58%). The most common adverse events reported were gastrointestinal symptoms. CDR scale showed reduced progression of cognitive decline (SMD = −0.4127, 95% CI: [−0.5926; −0.2327]), without subgroup differences between different dietary supplement interventions. ADCS‐ADL, MMSE, ADAS‐cog, adverse events, and ventricular volume did not demonstrate significant differences. However, Souvenaid® showed a significant negative effect (SMD = −0.3593, 95% CI: −0.5834 to −0.1352) in ventricular volumes. Conclusions The CDR scale showed reduced progression of cognitive decline among patients with n‐3‐PUFA supplemental interventions, with no differences between different n‐3‐PUFA supplements.